The Legal Value of Indirect Clauses Restricting the Provisions of Guaranteeing Latent Defect in Sales - عبد الكريم محمود; دوديـــن محمود (Journal of Legal Sciences, 2020)
The study addresses a set of indirect clauses that exempt from guaranteeing latent defect in sale contracts, in particular contracts between professional and consumer or normal contractor. The analytical comparative method has been adopted in this study through tackling the viewpoints of scholars and judiciary, and analyzing these in the framework of the Mejeleh, applicable in Palestine, along with the civil codes of Egypt, Jordan and Qatar. The study seeks to derive the legal value of the contractual clauses under consideration, and to indicate to what extent the legislator and judiciary contributed in achieving the economic balance of the contract between the two parties.